English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

7+(-9)+(-5)+6 I need to know what to do step by step thats the only way that i can understand

2007-04-25 08:46:05 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

7 + ( -9) + ( -5) + 6 start with the first two

7 +(-9) is 7 + -9 = -2

-2 + -5 = -7

-7 + 6 = -1

2007-04-25 08:54:13 · answer #1 · answered by kale_ewart 5 · 0 0

7+-9=-2+-5=-7+6=-1

2007-04-25 16:04:26 · answer #2 · answered by Dave aka Spider Monkey 7 · 0 0

The way to understand it is: when you have a negative and a postive number, subtract the absolute values (the "number without the sign") and keep the sign of the highest number; when you have 2 positives or 2 negatives, you add the absolute values and keep the sign.

So: 7+(-9) = -2
-2 + (-5) = -7
-7 + 6 = -1

2007-04-25 15:56:53 · answer #3 · answered by Enrique B 2 · 0 0

=7-9-5+6
7-9=-2
-5+6=1
therefore
7-9-5+6=-2+1= -1

2007-04-25 15:54:46 · answer #4 · answered by icingonthecake 2 · 0 0

ok let me see if you are asking it right. you want to add positive (+) 7 to a negative (-9) to a negative (-) 5 to a positive (+) 6

ok first you take the 7 and the -9 and you will get a negative (-) 2

then you add the negative (-) 5 and get negative (-) 7

add the positive (+) 6 and you will end with negative (-) 1

negative (-) 1

2007-04-25 15:58:41 · answer #5 · answered by jamz 5 · 0 0

fedest.com, questions and answers